East Asia rising. - Kumagai, J. (IEEE spectrum)
If the 19th century belonged to Britain and the loth century to the United States, the 21st century will surely be East Asia's. Already, South Korea, Taiwan, the eastern industrial areas of China, and Japan form an increasingly integrated economic bloc that rivals both Western Europe and the United States. Within decades, the region will become the world's dominant economic force.